Why People Hate Congress but Love Their Own Congressperson: An Information Processing Explanation. (March 2022) - Lammers, Joris; Pauels, Eileen; Fleischmann, Alexandra; Galinsky, Adam D.
Citizens in Western democracies often have negative attitudes toward political bodies, yet consistently re-elect their own representatives to these same political bodies. They hate Congress, but love their own congressperson. In contrast to resource-based explanations, we propose that this Paradox of Congressional Support is partly due to the wide availability of negative information about politicians in open societies combined with basic processes of information processing. Five studies found that unrelated negative political information decreases attitudes toward political categories such as U.S. governors but has no effect on attitudes of familiar, individual politicians (e.g., one's own governor); additional studies further identify familiarity as the critical process. Importantly, we demonstrate that this effect generalizes to all U.S. regions and remains when controlling for and is not moderated by political ideology. These results place a presumed macrolevel political paradox within the domain of cognitive mechanisms of basic information processing.